Early onset epilepsy and inherited metabolic disorders: diagnosis and management - Prasad, Asuri; Hoffmann, Georg F. (The journal, 2010)
Epileptic encephalopathies presenting in early life present a diagnostic and therapeutic challenge. These disorders present with multiple seizure types that are treatment resistant and associated with significant abnormalities on electroencephalographic studies. The underlying etiology in many cases may be related to an inborn error of metabolism. Efforts to establish the specific diagnosis of a genetic defect or an inborn error of metabolism often results in requests for a vast array of biochemical and molecular tests leading to an expensive workup. In this review, we present the clinician with information that provides a rationale for a selective and nuanced approach to biochemical assays, and initial treatment strategies while waiting for a specific diagnosis to be established. A careful consideration of the presentation, identification of potentially treatable conditions, and consultation with the biochemical genetics laboratory can lead to a greater measure of success while limiting cost overruns. Such a targeted approach is hoped will lead to an early diagnosis and appropriate interventions.